POTENSI RIZOBAKTERI INDIGENOUS ULTISOL UNTUK MENGENDALIKAN PENYAKIT BUSUK BATANG PHYTOPHTHORA (Phytophthora capsici) PADA TANAMAN CABAI. - Khaeruni, Andi; Sutariati, Gusti Ayu Kade; Rahman, Abdul (Jurnal Agroteknos, 2011)
The major problems to use the ultisol land in Southeast Sulawesi are low pH, poor nutrients  and  Fusarium  wilt  disease  suppression.      Plant  growth-promoting and bioprotecting rhizobacteria (PGPBR) is one of the few possibilities to overcome these problems. The objectives of this experiment were to evaluate the potency of ultisol indigenous rhizobacteria to control Phytophthora stem rot disease on chili pepper. Evaluation was conducted using five isolates of rhizobacteria (ST17c, ST26c, SS15b, SS16b & SS29a), as biological control agents treatments, compared to control treatment. The results indicated that application of ultisol indigenous rhizobacteria on seed and chili pepper rhizosfer significantly increased plant height and reduced disease incidence and disease severity of Phytophptora stem rot disease in chili pepper, compared to control. The best result was by the application of ST26c isolate, resulted in no disease symptoms developed during this experiment and significant increase in plant height to 32.28 centimeter at six week after planting. Key words: rizobacteria, Phytophthora capsici, Phytophthora stem rot disease